Acoustic target strength (TS) of argentine anchovy (Engraulis anchoita): The nighttime scattering layer - Madirolas, Adrian Osvaldo (2017)
Engraulis anchoita is a physostomous fish with a dual chambered swimbladder (sb). In situ target strength (TS) measurements on this species are only possible at night, when anchovies disperse forming a scattering layer near the sea surface. A survey data series comprising more than 50000 single target detections, recorded from 1995 to 2008, was analyzed in order to study the species specific TS at 38 kHz. A TS vs. fish total length (L) equation was obtained from the in situ measurements (TS = 31.9 log L - 82.4 dB; r 2 = 0.78). When the slope of the regression line was forced to 20 into the TS equation, the resulting value for the constant term (b 20) was -'68.6 dB. In any case, these results indicate an average difference of +3 dB (higher TS values) when compared with the general model suggested for clupeoid fish. The TS measurements obtained inside the nighttime sound scattering layer exhibited a negative trend with depth. An empirical depth dependence term for the anchovy TS equation was obtained through a three parameter least square fitting of the data [TS = 31.3 log L - 79.6 dB - 4.74 log (1 + z/10); r 2 = 0.74]. Anatomical data obtained through high resolution X-Ray Computed Tomography was employed as input for a Prolate Spheroidal Model (PSM). Theoretical TS vs. tilt angle functions were obtained considering the compression of the sb at different depths and under the assumption of different contraction rates. The TS functions were then averaged over different fish tilt angle distributions and used to derive theoretical depth dependence curves of average fish TS. The implications of the adopted sb contraction rate and tilt angle distribution are discussed by comparing the modelled TS(z) curves against the empirical data.